Enklave Bahasa Jawa di Provinsi Bengkulu: Kajian Dialektologi Diakronis - Anggy Denok Sukmawati (Balai Bahasa Provinsi Papua, 2019)
This research of Javanese Enclave of Bengkulu Province: A Study of Diachronic Dialectology aims to make synchronic and diachronic description of the Java language found in the enclave of Bengkulu. The study took two observation points, Kemumu village and Tangsi Duren village. Data collection is performed by field data collection research method with field notes and records technique. The primary data used for the analysis is obtained by structured interviews using the Cultural Basic Vocabulary. Analysis data was performed with quantitative and qualitative approaches. Data were analyzed synchronically from the level of phonology, lexicon, morphology, morphophonetics, and syntax. The results are then compared with each other to get the typical characteristics found in the Java language on the original region and in the enclave of Bengkulu Province. Furthermore, the data were analyzed diachronical ly to determine the level of kinship between dialect-subdialect in the Java language in Bengkulu Province, this research used comparative methods with lexicostatistics technique. The results of data analysis are presented using words and tables.From the analysis that has been done, it seems that there are no significant differences between BJEB with the Javanese language in the original region. The most visible differences are on the lexical level. At the lexical level, there are many Javanese words that have been replaced by Indonesian words. Another difference visible is the abandonment of the use of speech level by the Javenese community in Bengkulu enclave in everyday conservation. Thus, it can be concluded that BJEB is not significantly changed when compared to the Javanese language in the original region, but it experienced a worsening developments. The worsening developments can be seen from the abandonment of the Javanese language and the numbers of users are lesser and lesser.